A study on flow field analysis between ship to berth interaction - Chan, Kang Wai (2019)
In the marine industry, use of mooring line is a common application for docking a vessel to the shore, however, this causes the vessel to have a complex interaction with the bank which lead to the failure of the mooring line. This phenomenon involves the pressure and shallow water effect which generates a pulling and pushing force effect. If the experiment is conducted using real model, it is not cost effective and the whole experiment will take a very long duration to have some data and also such operation involved safety risks such as the ship hull damages, personnel safety as accident may occur. Therefore, the investigation of the effect of the interaction, numerical approach is chosen and ANSYS FLUENT is used to carry out the investigation. The analysis consists of a ship dock close to the pier where different settings were carried out to obtain the results for the ship hull and mooring line which can be used for reference in real life case. In this experiment, the aim is to understand how the dependent variables such as wave elevation at different wave amplitude and period which influences the forces and pressure exert on the ship hull, the tension experience by the mooring line and lastly, when the tension exceed the mooring line capacity till failure. The result achieve is able to let user understand the forces experience by the mooring line and also the duration where failure occurs.